Stochastic Dynamics of Gene Switching and Energy Dissipation for Gene Expression - Liu, Quan; Yu, FengZhen; Yi, Liang; Gao, Yijun; Gui, Rong; Yi, Ming; Sun, Jianqiang (Frontiers in Genetics, 2020)
Stochastic dynamics of gene switching and energy dissipation for gene expression are largely unknown, mainly due to the complexity of non-equilibrium mechanisms. Here, based on an important double-deck loop model, the stochastic mechanisms of gene switching and energy dissipation are studied. First, the probability distributions of steady states are calculated theoretically. It is found that the signal can strengthen the choice of gene switching between the “off” and “on” states. Our analysis of energy consumption illustrates that, compared with the synthesis and degradation of proteins, the process of gene switching costs little energy. Our theoretical analysis reveals some interesting insights into the determination of cell state and energy dissipation for gene expression.